2009
DOI: 10.1105/tpc.108.064865
|View full text |Cite
|
Sign up to set email alerts
|

The ESCRT-Related CHMP1A and B Proteins Mediate Multivesicular Body Sorting of Auxin Carriers inArabidopsisand Are Required for Plant Development

Abstract: Plasma membrane proteins internalized by endocytosis and targeted for degradation are sorted into lumenal vesicles of multivesicular bodies (MVBs) by the endosomal sorting complexes required for transport (ESCRT) machinery. Here, we show that the Arabidopsis thaliana ESCRT-related CHARGED MULTIVESICULAR BODY PROTEIN/CHROMATIN MODIFYING PROTEIN1A (CHMP1A) and CHMP1B proteins are essential for embryo and seedling development. Double homozygous chmp1a chmp1b mutant embryos showed limited polar differentiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
189
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(197 citation statements)
references
References 84 publications
(137 reference statements)
6
189
1
1
Order By: Relevance
“…This has indeed been shown for yeast ESCRTs, where the disassembly of ESCRT-III, but not of earlier ESCRTs, is strictly dependent on the AAA-ATPase Vps4 (Nickerson et al, 2010). SKD1, the Arabidopsis homolog of Vps4, localizes to MVBs/LEs (Haas et al, 2007) and interacts with ESCRT-III and ESCRT-associated proteins, but not with ESCRT-I or -II subunits (Spitzer et al, 2009;Shahriari et al, 2010). Therefore, the localization of the ESCRT-III subunit VPS2 at the MVB/LE is in agreement with the localization of the ESCRTassociated AAA-ATPase.…”
Section: Molecules Involved In Mvb Maturation: Rabs Escrt and Annexinsmentioning
confidence: 89%
See 1 more Smart Citation
“…This has indeed been shown for yeast ESCRTs, where the disassembly of ESCRT-III, but not of earlier ESCRTs, is strictly dependent on the AAA-ATPase Vps4 (Nickerson et al, 2010). SKD1, the Arabidopsis homolog of Vps4, localizes to MVBs/LEs (Haas et al, 2007) and interacts with ESCRT-III and ESCRT-associated proteins, but not with ESCRT-I or -II subunits (Spitzer et al, 2009;Shahriari et al, 2010). Therefore, the localization of the ESCRT-III subunit VPS2 at the MVB/LE is in agreement with the localization of the ESCRTassociated AAA-ATPase.…”
Section: Molecules Involved In Mvb Maturation: Rabs Escrt and Annexinsmentioning
confidence: 89%
“…Expression of a mutant form of Vps4 (SKD1) leads to the missorting of vacuolar proteins (Shahriari et al, 2010) as well as to an enlargement of MVBs with fewer ILVs (Haas et al, 2007). A reduction in number of ILVs and a displacement of cargo molecules destined for vacuolar degradation to the boundary membrane of the MVB was also observed after expression of mutated forms of the ESCRT-associated CHMP1A/B proteins (Spitzer et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Known targets of the endocytic trafficking route in plants include the auxin carriers PIN1, PIN2, and AUX1, the iron transporter IRT1, the boric acid/borate exporter BOR1, the flagellin receptor FLS2, the brassinosteroid receptor BRI1, and the high-affinity phosphate transporter PHT1 (Barberon et al, 2011;Bayle et al, 2011;Geldner et al, 2001;Kasai et al, 2011;Kleine-Vehn et al, 2006;Kleine-Vehn et al, 2008;Spallek et al, 2013;Spitzer, et al, 2009). (Slagsvold et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Putative homologs of all main ESCRT and ESCRT-related proteins have been identified in plants (Winter and Hauser 2006;Leung et al 2008;Spitzer et al 2009;Richardson et al 2011;Scheuring et al 2011;Shahriari et al 2011;Ibl et al 2012), some of which have been studied in detail.…”
Section: The Role Of the Escrt Machinery In Pm-protein Internalizatiomentioning
confidence: 99%
“…Spitzer et al (2009) described the function of putative CHMP1 orthologs from Arabidopsis. Apart from exhibiting severe seedling-lethal phenotypes, the authors demonstrated that a chmp1a chmp1b double mutant fails to internalize PIN auxin carriers into MVB vesicles, resulting in PIN mistargeting to the tonoplast rather than to the vacuolar lumen (Spitzer et al 2009).…”
Section: Degradative Sorting and Ubiquitylation Of Pin Proteinsmentioning
confidence: 99%